Numerical Investigation of Mixing Performance in Microfluidic Chip via Structural Micro-Rotors - Yongliang Dong; Liqiu Wang; Xing Han (Micromachines, 2025)
Microfluidics is a powerful tool with extensive applications, including chemical synthesis and biological detection. However, the limited channel size and high viscosity of samples/reagents make it difficult to fully mix liquids and improve the reaction efficiency inside microfluidic chips. Active mixing by rotors has been proven to be an effective method to promote mixing efficiency via a magnetic field. Here, we numerically investigated the mixing performance of rotors with different shapes (bar-shaped, Y-shaped, and cross-shaped). We systematically studied the influence of the arrangement of multiple cross-rotors and the rotation rate on mixing performance. The results are promising for instructing the design and manipulation of rotors for in-channel mixing.